Ability of rumen protozoa Diploplastron affine to utilize β-glucans - Belzecki, Grzegorz; Miltko, Renata; Michalowski, Tadeusz (Folia microbiologica, 2012)
The ability of the rumen ciliates to utilize β-glucans other than cellulose and xylan is currently being recognized. The objective of the present study was to characterize the ability of the ciliate Diploplastron affine to digest some pachyman, laminarin, pustulan, curdlan and lichean. The protozoa were isolated from the rumen of sheep and either grown in vitro or inoculated into the rumen of ciliate-free sheep and maintained in natural conditions. In vitro culture studies showed that the enrichment of culture medium with the examined saccharides results in an increase in the number of ciliates in comparison to the control cultures. The increase was over 36 and 15 % when the growth medium was supplemented with pachyman (1,3-β-glucan) and pustulan (1,6-β-glucan), respectively. A positive correlation was also found between the population density of ciliates and the dose of saccharide supplemented to the growth medium. Enzyme studies were performed using the crude enzyme preparation obtained from ciliates treated with antibiotics. The ability of ciliates to digest the examined β-glucans was tested by the quantification of reducing sugars released from the mentioned substrates during the incubation with crude enzyme preparation. The results showed that D. affine ciliates were able to digest both of them. The mean degradation rate varied between 6.7 and 28.2 μmol/L glucose per mg protein per h for pustulan and lichean, respectively, whereas the digestion velocity was the highest at 5.0-5.5 pH and 45-50°C.
Keywords: Animals; ovce; Protozoan Proteins; Rumen; protozoální proteiny; zvířata; beta-Glucans; Ciliophora; Sheep; bachor; beta-glukany